Linkage to HIV care and early retention in HIV care among men in the 'universal test-and-treat' era in a high HIV-burdened district, KwaZulu-Natal, South Africa - Mbuzeleni Hlongwa; Wisdom Basera; Khumbulani Hlongwana; Carl Lombard; Ria Laubscher; Sinegugu Duma; Mireille Cheyip; Debbie Bradshaw; Edward Nicol (BMC, 2024)
Abstract Introduction Despite the numerous efforts and initiatives, males with HIV are still less likely than women to receive HIV treatment. Across Sub-Saharan Africa, men are tested, linked, and retained in HIV care at lower rates than women, and South Africa is no exception. This is despite the introduction of the universal test-and-treat (UTT) prevention strategy anticipated to improve the uptake of HIV services. The aim of this study was to investigate linkage to and retention in care rates of an HIV-positive cohort of men in a high HIV prevalence rural district in KwaZulu-Natal province, South Africa. Methods From January 2018 to July 2019, we conducted an observational cohort study in 18 primary health care institutions in the uThukela district. Patient-level survey and clinical data were collected at baseline, 4-months and 12-months, using isiZulu and English REDCap-based questionnaires. We verified data through TIER.Net, Rapid mortality survey (RMS), and the National Health Laboratory Service (NHLS) databases. Data were analyzed using STATA version 15.1, with confidence intervals and p-value of ≤0.05 considered statistically significant. Results The study sample consisted of 343 male participants diagnosed with HIV and who reside in uThukela District. The median age was 33 years (interquartile range (IQR): 29-40), and more than half (56%; n = 193) were aged 18-34 years. Almost all participants (99.7%; n = 342) were Black African, with 84.5% (n = 290) being in a romantic relationship. The majority of participants (85%; n = 292) were linked to care within three months of follow-up. Short-term retention in care (≤ 12 months) was 46% (n = 132) among men who were linked to care within three months. Conclusion While the implementation of the UTT strategy has had positive influence on improving linkage to care, men's access of HIV treatment remains inconsistent and may require additional innovative strategies.